Answer:
The answer is option A
Step-by-step explanation:
<h3>
![( {x}^{ - \frac{4}{7} } )^{7}](https://tex.z-dn.net/?f=%28%20%7Bx%7D%5E%7B%20-%20%20%5Cfrac%7B4%7D%7B7%7D%20%7D%20%29%5E%7B7%7D%20)
</h3>
Using the rules of indices
That's
<h3>
![( { {a}^{x} })^{y} = {a}^{x \times y}](https://tex.z-dn.net/?f=%28%20%7B%20%7Ba%7D%5E%7Bx%7D%20%7D%29%5E%7By%7D%20%20%3D%20%20%7Ba%7D%5E%7Bx%20%5Ctimes%20y%7D%20)
</h3>
Simplify the expression
We have
<h3>
![( { {x}^{ - \frac{4}{7} } })^{7} = {x}^{ - \frac{4}{7} \times 7 } \\ = {x}^{ - 4}](https://tex.z-dn.net/?f=%28%20%7B%20%7Bx%7D%5E%7B%20-%20%20%5Cfrac%7B4%7D%7B7%7D%20%7D%20%7D%29%5E%7B7%7D%20%20%3D%20%20%7Bx%7D%5E%7B%20-%20%20%5Cfrac%7B4%7D%7B7%7D%20%5Ctimes%207%20%7D%20%20%20%5C%5C%20%20%3D%20%20%7Bx%7D%5E%7B%20-%204%7D%20)
</h3>
Again using the rules of indices
That's
<h3>
![{x}^{ - y} = \frac{1}{ {x}^{y} }](https://tex.z-dn.net/?f=%20%7Bx%7D%5E%7B%20-%20y%7D%20%20%3D%20%20%5Cfrac%7B1%7D%7B%20%7Bx%7D%5E%7By%7D%20%7D%20)
</h3>
The final answer is
<h3>
![\frac{1}{ {x}^{4} }](https://tex.z-dn.net/?f=%20%5Cfrac%7B1%7D%7B%20%7Bx%7D%5E%7B4%7D%20%7D%20)
</h3>
Hope this helps you
A)48
Explanation:
2^3 - 2^2 = 8 - 4 = 4
3^3 - 3^2 = 27 - 9 = 18
4^3 - 4^2 = 64 - 16 = 48
5^3 - 5^2 = 125 - 25 = 100
6^3 - 6^2 = 216 - 36 = 180
7^3 - 7^2 = 343 - 49 = 294
8^3 - 8^2 = 512 - 64 = 448
Answer:
![x=8](https://tex.z-dn.net/?f=x%3D8)
Step-by-step explanation:
Given
![AB||CD](https://tex.z-dn.net/?f=AB%7C%7CCD)
![\angle ABC = 5x + 50](https://tex.z-dn.net/?f=%5Cangle%20ABC%20%3D%205x%20%2B%2050)
![\angle BCD = 7x + 34](https://tex.z-dn.net/?f=%5Cangle%20BCD%20%3D%207x%20%2B%2034)
Required
Find x
If
i.e. If AB is parallel to CD, then
![\angle ABC = \angle BCD](https://tex.z-dn.net/?f=%5Cangle%20ABC%20%3D%20%5Cangle%20BCD)
Substitute values for ABC and BCD
![5x + 50 = 7x + 34](https://tex.z-dn.net/?f=5x%20%2B%2050%20%3D%207x%20%2B%2034)
Collect Like Terms
![5x - 7x = -50 + 34](https://tex.z-dn.net/?f=5x%20-%207x%20%3D%20-50%20%2B%2034)
![-2x = -16](https://tex.z-dn.net/?f=-2x%20%3D%20-16)
Multiply through by ![-\frac{1}{2}](https://tex.z-dn.net/?f=-%5Cfrac%7B1%7D%7B2%7D)
![-\frac{1}{2} * -2x = -16 * -\frac{1}{2}](https://tex.z-dn.net/?f=-%5Cfrac%7B1%7D%7B2%7D%20%2A%20-2x%20%3D%20-16%20%2A%20-%5Cfrac%7B1%7D%7B2%7D)
![\frac{1}{2} * 2x = 16 * \frac{1}{2}](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B2%7D%20%2A%202x%20%3D%2016%20%2A%20%5Cfrac%7B1%7D%7B2%7D)
![\frac{2x}{2} = \frac{16}{2}](https://tex.z-dn.net/?f=%5Cfrac%7B2x%7D%7B2%7D%20%3D%20%5Cfrac%7B16%7D%7B2%7D)
![x = \frac{16}{2}](https://tex.z-dn.net/?f=x%20%3D%20%5Cfrac%7B16%7D%7B2%7D)
![x=8](https://tex.z-dn.net/?f=x%3D8)
Answer:
2( 100%) +75%
Step-by-step explanation:
a full box will literally be 100%, so two full boxes will be 2 × a full ie 100%, 'and' a box ie 75% full is addition '+'